International Trends in Participatory Budgeting
XVIII, 317 p. 17 illus.
Keywords: This book analyses the participatory budgeting practice as it has evolved in evaluated countries, focusing on what is substantially at stake concerning the budget and issues involved, the actual participation, the way such processes are organised and administered, and the outcomes of such processes. It concludes that participatory budgeting in selected European countries is far away from the level of ‘best practice’, but that all experiences are not just trivial pursuits. The information collected serves to check, to what extent participatory budgeting as practiced in the countries involved presents a real attempt to change municipal budgets towards addressing the needs of marginalized groups and to improve decision-making based on local democracy and participation, or whether these processes as such are to be judged to be more important than any output and outcomes. The practices can neither be seen as a process of policy diffusion nor as a process of policy mimesis. The terminology of participatory budgeting remains, but the tools to achieve the goals resulted only in marginal changes in the status quo in municipalities in European countries practicing participatory budgeting, instead of resulting in radical changes to increase spending in favor of marginalized groups. Chapter 15 'Unraveled Practices of Participatory Budgeting in European Democracies' is available open access under a CC BY 4.0 license. Michiel S. de Vries is Full Professor of Public Administration at the Radboud University of Nijmegen, the Netherlands. Juraj Nemec is Professor of Public Finance and Public Management at the Faculty of Economics and Administration at Masaryk University in Brno, Czech Republic. David Špaček is Associate Professor at the Department of Public Economics, Faculty of Economics and Administration, Masaryk University, Brno, Czech Republic.